The Baller-Gerold syndrome: phenotypic and cytogenetic overlap with Roberts syndrome. Issue 6 (June 1990) - Huson, S M; Rodgers, C S; Hall, C M; Winter, R M
Abstract : A case is reported where the major clinical features of craniostenosis and radial aplasia led to an initial diagnosis of Baller-Gerold syndrome. Mild fibular hypoplasia on skeletal survey led to review of the diagnosis and the similarity of the facial phenotype to that of Roberts syndrome was noted. Chromosome analysis showed the premature centromere separation characteristic of this condition. This case raises the question as to whether the Baller-Gerold syndrome can be considered as a distinct entity. It is suggested that cases diagnosed as having Baller-Gerold syndrome should have cytogenetic analysis and that known Roberts syndrome survivors are reviewed for signs of craniostenosis.